Perceptions of the Health Care Workers about the Guideline Implemented for Safe Surgical Practice during COVID-19 Pandemic in a University Teaching Hospital - Iyer, Subramania; Subramaniam, Sobha; Thankappan, Krishnakumar; Rao, Nageswara; Satyapalan, Dipu; Ravikumar, Beena; Vasudevan, Anu (The Surgery Journal, 2021)
One area of health care delivery that has been affected badly in most of the institutions is the running of the surgical services. This is due to various factors such as the presence of asymptomatic carrier stage, increased morbidity and mortality in surgical procedures in a COVID-19 patient, and possible transmission of disease to the health care workers (HCWs). A guideline was formulated in our institution, which is a tertiary care university teaching hospital to resume the surgical activities in full. Following its implementation, a questionnaire-based study was conducted to understand the perception of the HCWs about the guidelines. The questionnaire had four domains with questions related to the impact of the epidemic on the practices, composition of the guidelines, its implementation, and effects. There were 217 responders which included doctors and the supportive staff. Majority of the responders welcomed the introduction of the guidelines, and felt that it ensured patient's safety and helped streamline the services. Quarantine and preoperative reverse transcription polymerase chain reaction testing were found to be appropriate measures by the respondents. In some areas, there was a difference in the responses from the doctors to that from the supportive group which assumed statistical significance. These included the reason for drop in patient numbers was the reduced patient accessibility which was felt mainly by the doctors. The doctors perceived a delay in carrying out the work, increased workload, and mental agony due to the presence of the guidelines.
Keywords: COVID-19 pandemic; guidelines; surgery